PENDIDIKAN MULTIKULTURALISME BERBASIS PEMBELAJARAN BERPUSAT PADA MAHASISWA: PERSEPSI MAHASISWA CALON GURU TENTANG EKSIBISI KELAS PROJECT-BASED LEARNING - Sadiq, Nizamuddin (Refleksi Pembelajaran Inovatif, 2025)
This paper investigates English pre-service teachers' perceptions of a project-based learning (PjBL) class exhibition as the output of a Multiculturalism in Language Learning (MLL) course. Employing a qualitative approach, this study analysed student reflections written specifically those related to the PjBL class exhibition. The data analysis was conducted using thematic analysis. The findings are categorized into three main themes: Valuable Experiences and Educational Benefits, Skill Development, and Engagement, Innovation, and Improvement. A limitation of this study is its reliance solely on student written reflections, without supplementary data from interviews. Therefore, for future research, it is recommended that interview sessions be incorporated to further elaborate on students' narratives. The findings of this study implies that reflection is an essential and integral component of the learning assessment process through project-based learning. Accordingly, the implementation of effective reflection mechanisms should be a key focus for teachers.